Tracing complexity from requirements to implementation - Arévalo, Gabriela Beatriz (2011)
Complexity metrics are useful measurements to ascertain the quality of software. However, the metrics are only applied and isolated in one specific development phase and they can not trace the quality (and the evolution) of the same software artifacts in all development phases within the context of the software lifecycle. In this paper, we propose a methodology to use a traceable metric to measure software artifacts from requirements to implementation in a system. We validate our approach on transactions defined in use cases and implemented in source code. Some initial results show that our approach can solve the problem of tracing software artifacts during the software development process.